The impact of multi-criteria performance measurement on business performance improvement - Fentahun Moges Kasie; Alemu Moges Belay (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The purpose of this paper is to investigate the relationship between multi-criteria performance measurement (MCPM) practice and business performance improvement using the raw data collected from 33 selected manufacturing companies. In addition, it proposes modified MCPM model as an effective approach to improve business performance of manufacturing companies. Design/methodology/approach:Research paper. Primary and secondary data were collected using questionnaire survey, interview and observation of records. The methodology is to evaluate business performances of sampled manufacturing companies and the extent of utilization of crucial non-financial (lagging) and non-financial (leading) performance measures. The positive correlation between financial business performance and practice of MCPM is clearly shown using Pearson's correlation coefficient analysis. Findings -This research paper indicates that companies which measure their performance using important financial and non-financial measures achieve better business performance. Even though certain companies are currently using non-financial measures, the researchers have learned that these financial measures were not integrated with each other, financial measures and strategic objectives. Research limitations/implications: The limitation of this paper is that the number of surveyed companies is small to make generalization and they are found in a single country. Further researches which incorporate a large number of companies from various developing nations are suggested to minimize the limitation of this research. Practical Implication: The paper shows that multi-dimensional performance measures with the inclusion of key leading indicator are essential to predict the future environment. But cost-accounting based financial measures are inadequate to do so. These are shown practically using Pearson's correlation coefficient analysis. Originality/value: The significance of multi-dimensional performance measures for business improvement in developing countries has been an issue among researchers. The originality of the paper is evident in the proposal of MCPM model, considering the problems being faced by some manufacturing firms leading to low performance.
Keywords: 650; performance measure; performance improvement; benchmark; business performance; manufacturing